Fishing activities by gender and reproductive stage in Isla Arena, Campeche, Mexico. (February 2018) - Uc-Espadas, Martha; Molina-Rosales, Dolores; Gurri, Francisco D.; Pérez-Jiménez, Juan Carlos; Vázquez-García, Verónica
Abstract: The following paper analyzes the impact of reproductive stage on gendered mediated productive activities, and access to fishing resources in 62 artisanal fishing households from Isla Arena, Campeche, Mexico. Male activities were independent of reproductive stage. Women with children and adolescents stayed within the household to process subsistence and commercial fish provided by other family members. Women without children or those with adult siblings did go out fishing in the sea and the estuary. In spite of their access to commercial fisheries, these women still did not have control of the catch, suggesting that childrearing is not the reason why women do not have direct access to this resource. Public policy aimed at women in small-scale fishery households should highlight the domestic domain in the case of women with children and bolster estuary subsistence fisheries where women can manage the catch independently. Highlights: In artisanal fisheries women's productive activities vary with reproductive stage. Only the activities of women with children in artisanal fisheries vary by gender. Women without children carry out the same activities as men. Childcare does not explain women's lack of control over commercial fisheries. Lumping women demographically has blurred the breadth of their participation.